Trends and Visualization of Soft Computing Research in Deep Learning - wahyu, enggarani (Jurnal Informatika dan Sains Media (JISMA), 2024)
The background of this research is the significant increase in the number of scientific publications related to the use of soft computing in Deep Learning in recent years. As bibliometric data becomes increasingly complex, an effective tool is needed to map and analyze this data. This research aims to provide a step-by-step analysis to make it easier for novice users to follow how to use VOSViewer. This report enables and facilitates data analysis by utilizing mapping tools and provides an analysis of the development of research on digital learning media. The method used in this research is to conduct bibliometric analysis to produce network visualization of co-work maps and co-work density maps. The analysis was conducted using the number of publications obtained, related to the specified topic, totaling 500 documents in 2017-2021. As a practical example, we evaluate Soft Computing in Deep Learning. This research method involves Deep Learning. The results of this study show significant insights into research trends and developments in digital learning media. The conclusion shows that VOSviewer can be used to provide suggestions in data analysis results.